2019
DOI: 10.1177/1076029618820167
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis for Hip Revision Arthroplasty: Can We Use the Recommendations for Primary Hip Surgery? A Cohort Study

Abstract: The risk of thromboembolic events after hip revision arthroplasty might be higher than in primary hip arthroplasty. However, evidence regarding the use of thromboprophylaxis in revisions is scarce. The purpose of this study is to determine whether thromboprophylaxis recommendations for primary arthroplasty produce similar results in hip revision arthroplasty. This comparative cohort study retrospectively analyzed consecutive patients undergoing primary hip arthroplasty and hip revision surgery between March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…21 It is worth emphasizing that the risk of VTE in revision arthroplasties is greater, as the magnitude and complexity of the procedure are considered to increase the risk of occurrence of this event. 12 We believe the use of the same protocol we used can determine the same positive results achieved in primary and revision THA. We did not observe any cases of DVT in the group of individuals undergoing revision THA.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…21 It is worth emphasizing that the risk of VTE in revision arthroplasties is greater, as the magnitude and complexity of the procedure are considered to increase the risk of occurrence of this event. 12 We believe the use of the same protocol we used can determine the same positive results achieved in primary and revision THA. We did not observe any cases of DVT in the group of individuals undergoing revision THA.…”
Section: Resultsmentioning
confidence: 82%
“…In general, we found studies whose methods are similar to those adopted by Torres, Bautista and Lins, with incidences ranging from 0% to 3%. [10][11][12]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictors of VTE Events in Revision Arthroplasty Knee and Hip Surgery: Multiple studies have compared the incidence of VTE in primary and revision THA and TKA. Comparing direct VTE rates between revision and primary arthroplasty surgery, some studies have observed no difference in VTE rates [394][395][396][397] , some have observed a decreased incidence 394 , and others have observed an increased incidence [398][399][400] . In the studies that observed a higher incidence of VTE in revision vs. primary arthroplasty surgery, when the rates were adjusted for risk factors and comorbidities, revision surgery was either not associated with a higher risk of VTE 398 , or had a lower difference based on risk stratification 401 .…”
Section: 45% (Strong Consensus)mentioning
confidence: 99%